Advances in services computing : 9th Asia-Pacific Services Computing Conference, APSCC 2015, Bangkok, Thailand, December 7-9, 2015, Proceedings /: 9th Asia-Pacific Services Computing Conference, APSCC 2015, Bangkok, Thailand, December 7-9, 2015, Proceedings. (2015) - Unknown
No abstract available